New Features in the Lipid A Structure of Brucella suis and Brucella abortus Lipopolysaccharide - Casabuono, Adriana Cristina (2017)
Brucellaceae are Gram-negative bacteria that cause brucellosis, one of the most distributed worldwide zoonosis, transmitted to humans by contact with either infected animals or their products. The lipopolysaccharide exposed on the cell surface has been intensively studied and is considered a major virulence factor of Brucella. In the last years, structural studies allowed the determination of new structures in the core oligosaccharide and the O-antigen of this lipopolysaccharide. In this work, we have reinvestigated the lipid A structure isolated from B. suis and B. abortus lipopolysaccharides. A detailed study by MALDI-TOF mass spectrometry in the positive and negative ion modes of the lipid A moieties purified from both species was performed. Interestingly, a new feature was detected: the presence of a pyrophosphorylethanolamine residue substituting the backbone. LID-MS/MS analysis of some of the detected ions allowed assurance that the Lipid A structure composed by the diGlcN3N disaccharide, mainly hexa-acylated and penta-acylated, bearing one phosphate and one pyrophosphorylethanolamine residue.